2021
DOI: 10.1039/d0cb00151a
|View full text |Cite
|
Sign up to set email alerts
|

DNA folds threaten genetic stability and can be leveraged for chemotherapy

Abstract: Alternative DNA structures (including G-quadruplexes and DNA junctions) represent promising targets for combinatorial chemotherapeutic treatments aiming at fostering genomic instability and impeding DNA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 419 publications
(526 reference statements)
1
48
0
Order By: Relevance
“…As G4s are intimately linked to genetic transactions (see section 2b), G4 ligands can stabilize physically barriers to polymerases in general, triggering DNA damage (Figure 4). (252,253) It may be more elegant to consider G4s as genetic switches with specific spatiotemporal control over key cellular processes, compared to considering G4s as genome-wide triggers for creating DNA damage, however this latter, simpler rationale offers a mechanistic model that accounts for most of the cell-based studies collected so far. Therefore, in light of the propensity of G4-stabilising ligands to trigger genetic instability, and the association with severe genetic dysregulations (see section 2c), it is surprising that, to date, most if not all efforts by chemical biologists have been focused on G4 stabilization rather than destabilization.…”
Section: B the Formation Of G-quadruplexes Is Intimately Linked To Genetic Transactionsmentioning
confidence: 99%
“…As G4s are intimately linked to genetic transactions (see section 2b), G4 ligands can stabilize physically barriers to polymerases in general, triggering DNA damage (Figure 4). (252,253) It may be more elegant to consider G4s as genetic switches with specific spatiotemporal control over key cellular processes, compared to considering G4s as genome-wide triggers for creating DNA damage, however this latter, simpler rationale offers a mechanistic model that accounts for most of the cell-based studies collected so far. Therefore, in light of the propensity of G4-stabilising ligands to trigger genetic instability, and the association with severe genetic dysregulations (see section 2c), it is surprising that, to date, most if not all efforts by chemical biologists have been focused on G4 stabilization rather than destabilization.…”
Section: B the Formation Of G-quadruplexes Is Intimately Linked To Genetic Transactionsmentioning
confidence: 99%
“…The relationship between G4 structures/motifs and the progressive discovery of proteins that modulate the dynamic of G4 formation, such as helicases or other proteins involved in DNA and RNA transactions has expanded our knowledge to understand the ubiquitous function of G4 structures on cellular metabolism and cell fate 5 , 6 , 13 , 15 , 17 20 , 64 . In the present study, we identified through a MS-based quantitative proteomic analysis 425 human proteins significantly enriched on constrained G4 structures relative to a duplex DNA control, in which well-described G4 interacting factors were present.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between G4 structures/motifs and the progressive discovery of proteins that modulate the dynamic of G4 formation, such as helicases or other proteins involved in DNA and RNA transactions has expanded our knowledge to understand the ubiquitous function of G4 structures on cellular metabolism and cell fate 5,6,13,15,[17][18][19][20]64 . In the present study, we identified through a MS-based quantitative proteomic analysis 425 human proteins significantly enriched on constrained G4 structures relative to a duplex DNA control, in which welldescribed G4 interacting factors were present.…”
Section: Discussionmentioning
confidence: 99%